Metode Pembelajaran Berbasis Belajar Mandiri (Self Directed Learning)Pada Pendidikan Keperawatan: A Literature Review - Yuliana, Nuriyah; Kusumawati - Universitas Muhammadiyah Yogyakarta, Wiwik (IJMS - Indonesian Journal on Medical Science, 2019)
Abstract: Education must be able to provide sufficient hard skills and soft skills to students to face the increasing challenges of life in the era of globalization (including MEA) both now and in the future. One of the soft skills competencies that are important to be trained is self-directed learning and is one indicator of nursing education competencies, namely life-long learning. The purpose of this study was to analyz of journals regarding the application of the method of self-directed learning in improving the competence of nursing students.This study is a literature review research that focuses on the results of writing relating to the application of the method of self-directed learning to nursing students through searching of accredited journal sites such as ProQoest, PubMED, ResearchGate, SagePub and Schoolar with keywords self-directed learning education, competency, learning outcome in the period 2013-2018. That data has been obtained is reviewed, compared, arranged systematically, and discussed.It was found that 3,240 journals identified based on the keywords which were then filtered so that 28 journals based on inclusion criteria were obtained, filtered again for eligibility and found the total articles that qualified for review were 11 journals. The influence of the application of self-directed learning methods on competency of nursing students was found, including increase in critical thinking skills, communication effective, interpersonal skill, self-efficacy, sense of responsibility, motivation, outonomi, self-confidence, academic value, independence and creativity. Keywords: Self-Directed Learning, competency, nursing student Abstrak: Pendidikan harus dapat memberikan bekal hard skill dan soft skill yang memadai kepada peserta didik untuk menghadapi semakin meningkatnya tantangan kehidupan di era globalisasi (termasuk MEA) baik masa sekarang maupun yang akan datang. Salah satu kompetensi soft skill yang penting dilatih adalah self-directed learning dan merupakan salah satu indikator dari kompetensi pendidikan keperawatan yaitu pembelajaran sepanjang hayat (life-long learning). Tujuan dari studi ini untuk menganalisis jurnal mengenai penerapan metode self-directed learning dalam meningkatkan kompetensi mahasiswa keperawatan.Penelitian ini adalah penelitian studi literatur review yang berfokus pada hasil penulisan yang berkaitan dengan penerapan metode self directed learning pada mahasiswa keperawatan melalui penelusuran situs jurnal yang sudah terakreditasi seperti ProQoest, PubMED, ResearchGate, SagePub dan Schoolar dengan kata kunci self-directed learning, nursing education, competency, learning outcome dalam kurun waktu 2013-2018. Data yang telah diperoleh ditelaah, dibandingkan, disusun secara sistematis, dan dibahas. Didapatkan 3.240 jurnal diidentifikasi berdasarkan kata kunci yang kemudian disaring sehingga didapatkan 28 jurnal berdasarkan kriteria inklusi, disaring lagi kelayakannya dan didapatkan total artikel yang memenuhi syarat untuk review adalah 11 jurnal. Ditemukan adanya pengaruh penerapan metode pembelajaran self-directed learning terhadap kompetensi mahasiswa keperawatan, diantaranya adalah meningkatnya kemampuan meningkatnya kemampuan berfikir kritis, komunikasi efektif, kemampuan interpersonal, self-efficacy, tanggung jawab, motivasi, otonomomi, rasa percaya diri, nilai akademik, kemandirianserta kreatifitas.Kata Kunci: Self Directed Learning, Kompetensi, Mahasiswa Keperawatan